Peran orang tua pada pembelajaran daring di masa pandemi dalam meningkatkan kualitas belajar Siswa Kelas 1 SDN Sarimulyo 02 - Ika Maharani; Deka Setiawan; Much. Arsyad Fardhani (IKIP Siliwangi, 2023)
This study aims to describe the efforts of parents to improve the quality of learning for grade 1 students at SD N Sarimulyo in online learning during the pandemic. . Data collection techniques include the stages of observation, interviews, documentation. Data analysis includes data collection, data reduction, data presentation, data verification or drawing conclusions. The results showed that the efforts of parents to improve the quality of learning for grade 1 students at SD N Sarimulyo in online learning during the pandemic were to carry out the functions of parents as teachers, parents as facilitators, parents as motivators, parents as directors. As teachers, parents have the task of guiding children during online learning from home and participating in the learning process, for example understanding questions to help children learn. As facilitators, parents provide learning facilities such as stationery, textbooks to facilitate children in the learning process and facilities and infrastructure, for example providing quotas for the implementation of online learning. As a motivator, parents encourage children to carry out online learning. As directors, parents direct children according to their respective talents and interests.